Factors Affecting the Outcome after Surgical Clipping of Ruptured Distal Anterior Cerebral Artery (DACA) Aneurysms - Sharma, Gopal Raman; Karki, Prasanna; Joshi, Sumit; Paudel, Prakash; Shah, Damber Bikram; Baburam, Pokharel; Bidhan, Gyawali (Asian Journal of Neurosurgery, 2023)
Objective The purpose of this study is to assess demographic, clinical, and unique morphological characteristics of distal anterior cerebral artery (DACA) aneurysm. The relation of outcome included Glasgow Outcome Scale (GOS) using various independent variables, Hunt and Hess clinical grade (H&H), Miller Fischer grade, intraoperative rupture, and comparison of outcomes at discharge and last follow-up.Methods Demographic data, aneurysm characteristics, and treatment outcomes were evaluated in 28 ruptured DACA aneurysms operated over a period of 13 years. Association between independent variables and dependent variables (GOS) at discharge and at last follow-up (13 years) was analyzed, and the interrelationship between these factors and outcome was evaluated. GOS was used to assess functional outcomes.Results Over a period of 13 years, 500 patients harboring ruptured intracranial aneurysms were surgically clipped, and out of them 28 patients (5.6%) had ruptured DACA aneurysms. In this series, 20 (71.4%) patients had low grade and 8 (28.6%) had high grade H&H. Out of the 28 patients, 19 (67.8%) had good recovery, 6 (21.5%) were severely disabled, and 3 (10.7%) died at the time of discharge. On the last follow-up (13 years), smoking (p-value 0.03) and use of temporary clip (p-value 0.00) were significant predictors for unfavorable outcome.Conclusion The results of our case series show that even with ruptured aneurysm excellent overall outcome after microsurgical clipping can be achieved, even though among cerebral aneurysms, DACA aneurysm is considered to have less favorable outcome. Alcohol consumption and use of temporary clip were the predictors for unfavorable outcome at the time of discharge. On the last follow-up, smoking and use of temporary clip were found to be the risk factors for unfavorable outcome. Although the small sample size of this study is a limitation, smoking and use of temporary clip play an important role on the overall outcome. The aim of this study was to analyze data to determine factors which may influence outcome after surgical clipping of ruptured DACA aneurysms.
Keywords: anterior circulation; cerebral aneurysm; microsurgical clipping; Hunt and Hess grade; functional outcome